Analisis Faktor Penentu Preferensi Masyarakat Milenial Dalam Menggunakan Sistem Pembayaran Secara Cashless Di Tangerang Selatan - Husnayetti, Husnayetti; Sestri, Ellya; Novida, Irma (ITB Ahmad Dahlan Jakarta, 2020)
The study focuses on the determinants of the millennial community preference in using cashless payment. The aim of research to identify factors that considered the millennial to use cashless payment. In theory, the factors that encourage people to adopt and use electronic payment system as follows: Socio-demographic consisting of age, sex, education and language, Financial, Technology (frequency of use of mobile banking phone, a personal computer, the Internet, PDAs and the use of the service over the phone) and Supply-side by counting the number of POS (Pont Off Sale) and ATM. Furthermore, the high range of the technology and the Internet and systems digital payment (cashless)The earliest touching the millennial so in this study conducted in the millennial who use cashless payment in South Tangerang method is purposive sampling, the data obtained through questionnaires distributed to 100 respondents. The questionnaire prepared by the Likert scale and analyzed using factor analysis and descriptive analysis. From the results of the study showed that the determinants of the millennial use payment cashless is the ability of financial (X1) with a loading factor 0.736, Convenience Payment (X2) with loading factor of 0.732, Ease of transacting (X3) with a value of 0.875 and Special Promo (X4) with a value of 0.826-factor loading.